The Influence of Customs in the Sanctioning of Islamic Law and State Law in Malaysia - Mohamad, Mohd Nasran bin; Ismail, Ismail (Alhurriyah, 2023)
This research aims to examine how Malaysia strives to harmonies the formulation of Civil law, Shariah law, and customary law in its legal system. In 1422, the Law of the Malacca Code was Islamic law and a custom practiced and spread into the Law of the Pahang Code, the Law of Kedah, and the Law of 99 Perak. After the arrival of the British in Malaya, one of the conditions of Malaysia's independence was the adoption of English law based on Common Law with Islam as the official religion of the Federation of Malaysia. This study concludes that first, customary law exerted a significant influence in the formation of laws in Malaysia, as evidenced by the development of laws in Malaysia through the pre-colonial phase of the British occupation, which practiced Islamic law mixed with customary laws, and phases after British colonialism. Second, the global situation in Malaysia does not weaken the development of Islamic law through sanctions, so the relationship between Islamic law and Customs is strengthened by the Malaysian customary constitutional system, Islamic family law, and Islamic jinayah law.Penelitian ini bertujuan untuk mengkaji bagaimana Malaysia berusaha mengharmonikan penggubalanÂ  undang-undang Sivil, undang-undang Shariah dan undang adat dalam sistem undang-undang nya. Pada tahun 1422 Hukum Kanun Melaka adalah undang-undang Islam dan adat yang diamalkan dan tersebar menjadi Hukum Kanun Pahang, Undang-undang Kedah dan Undang-undang 99 Perak. Setelah kedatangan British di Tanah Melayu, salah satu syaratÂ  kemerdekaan Malaysia ialah penerimaan undang-undang Inggeris berasaskan Common Law dengan Islam sebagai agama rasmi bagi Persekutuan Malaysia. Penelitian ini menyimpulkan bahwa pertama, hukum adat memberikan pengaruh yang signifikan dalam pembentukan undang-undang di Malaysia dibuktikan dengan perkembangan undang-undang di Malaysia melalui fase sebelum penjajahan British yang mengamalkan undang-undang Islam bercampur dengan undang-undang adat dan fase setelah penjajahan Inggeris. Kedua, situasi global di Malaysia tidak membuat pelemahan terhadap perkembangan hukum Islam melalui pengkanunan, justru antara hukum Islam dan hukum Adat mengalami penguatan pada sistem perlembagaan adat Malaysia, undang-undang kekeluargaan Islam dan undang-undang jinayah Islam.